Localized electrons in dense heavy noble gases - Nazin, S.; Shikin, V. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2009)
The paper addresses counterintuitive behavior of electrons injected into dense cryogenic media with negative scattering length a0. Instead of expected polaronic effect (formation of density enhancement clusters) which should substantially reduce the electron mobility, an opposite picture is observed: with increasing |a0| (the trend taking place for inert gases with the growth of atomic number) and the medium density, the electrons remain practically free. An explanation of this behavior is provided based on consistent accounting for the non-linearity of electron interaction with the gaseous medium in the gas atom number density.